Iron Cage Birokrasi Pendidikan: Suatu Analisis Sosiologis - Siti Ikramatoun; Khairul Amin; Darwin; Halik (Faculty of Social Science, Universitas Negeri Malang, 2021)
This article aims to describe the education bureaucracy as a tool to achieve the objectives of education through a qualitative approach to the literature study model. The data in this paper is sourced from relevant literature and the author's experience while active in educational activities. The results of this study indicate that the bureaucracy in the form of educational administration has changed to an iron cage that shackles the educational activity itself. The delivery of education loses its orientation and turns into ceremonial routines to meet the demands of the bureaucracy. Various training, capacity building, and teacher competence have been done, but they have not significantly changed the face of education. Iron cage bureaucracy makes teachers